STUDIES ON INDUSTRIAL BOILER EFFICIENCY: THERMAL ANALYSIS AND NDT - Cristian-Vladimir Godoroja; Ionel Simion (Journal of Industrial Design and Engineering Graphics)
To maximize the performance and safety of industrial boilers, this research examines their efficiency, highlighting the importance of thermal analysis and non-destructive testing (NDT). The study shows that careful design of pressure components and temperature and heat transfer calculations lead to higher thermal efficiency. It also examines non-destructive testing methods for finding structural flaws, emphasizing their importance in preventing failures and ensuring long-term, peak performance. The study's findings highlight how rigorous implementation of these techniques can significantly increase the operational safety and energy efficiency of industrial boilers.